Changes in influenza-associated excess mortality in China between 2012–2019 and 2020–2021: a population-based statistical modelling study - Xiaowei Deng; Jiangmei Liu; Minghan Wang; Nana Chen; Feiran Hao; Juan Yang; Maigeng Zhou; Hongjie Yu (Infectious Diseases of Poverty)
Abstract Background The seasonal cycle of the influenza virus causes substantial morbidity and mortality globally. The impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on the circulation of influenza viruses can influence influenza-associated excess mortality. Given the few studies that have explored this topic, the objective of this study was to evaluate influenza-associated excess mortality in the Chinese mainland from 2012 to 2021 and quantify the changes from 2020 to 2021 compared with 2012–2019. Methods Using data from national influenza surveillance report and disease surveillance points, we fitted a generalized additive model on all-cause (AC), pneumonia & influenza (P&I), and respiratory (R) mortality rates. In this model, we included data of influenza activity (A/H1N1, A/H3N2 and B), temperature, absolute humidity, the COVID-19 pandemic, and time trends. The excess mortality was estimated by subtracting the fitted baseline mortality from the predicted mortality, which set influenza activity to zero. Results The respiratory mortality model explained more than 90% of the variance, indicating the good performance. We found that the influenza-associated mortality was generally decreasing from 2020 to 2021, for instance, influenza A/H1N1-associated excess respiratory mortality (ERM) decreased from 2.62 per 100,000 persons (95% confidence interval: 0.16–5.21) to 0.31 (0.02–0.60) in the northern region and from 3.79 (0.09–7.05) to 0.24 (0.02–0.46) in the southern region between 2012–2019 and 2020–2021. A similar pattern was observed for A/H3N2-associated ERM. While the influenza B remained similar scale, for instance, the ERM was 2.90 (0.72–4.3) and 2.26 (1.76–2.76) in the southern region between 2012–2019 and 2020–2021, respectively. Distinct pattern was observed for the AC and P&I outcomes. Conclusions The COVID-19 pandemic has reduced influenza-associated excess mortality, which may be a result of the reduced activity of the influenza virus caused by nonpharmaceutical interventions. Different patterns of regional differences differed for influenza-associated AC, P&I and R mortality. It should be noticed that the contribution of influenza B was generally similar when comparing 2012–2019 and 2020–2021, which highlighted the attention on the influenza B activity. Additional studies are needed to explore the changes in influenza-associated excess mortality afterwards.